1975
DOI: 10.1093/oxfordjournals.aje.a112077
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Disease of University Students With Special Reference to the Etiologic Role of Herpesvirus Hominis

Abstract: Infections with Herpesvirus hominis type 1 were associated with 11.5% of acute respiratory illnesses of university students who were admitted to the student infirmary over a 6-year period. Over three-quarters of these infections were detected in students with pharyngitis or tonsillitis; 42% had ulcerated lesions on tonsils or posterior pharynx but only 11% had lesions in the anterior portion of the mouth or lips. Almost all of the H. hominis infections were accompanied by significant rises in neutralizing anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…Similarly, a cohort of 14-to 15-year-olds who were monitored for 15 years initially had a 25% seropositivity for HSV-1, but had a 59% seropositivity 15 years later (6). A 1975 university-based study of HSV respiratory disease indicated that only 30% of incoming students initially had HSV-1 antibodies, but there was an approximate 10% annual rate of seroconversion noted in this population (13). Of note, in a recent study looking at 124 healthy 17-to 24-year-olds in Central Kentucky, only 35.1% of the 17-to 19-year-olds had antibodies to HSV-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a cohort of 14-to 15-year-olds who were monitored for 15 years initially had a 25% seropositivity for HSV-1, but had a 59% seropositivity 15 years later (6). A 1975 university-based study of HSV respiratory disease indicated that only 30% of incoming students initially had HSV-1 antibodies, but there was an approximate 10% annual rate of seroconversion noted in this population (13). Of note, in a recent study looking at 124 healthy 17-to 24-year-olds in Central Kentucky, only 35.1% of the 17-to 19-year-olds had antibodies to HSV-1.…”
Section: Discussionmentioning
confidence: 99%
“…HSV-1 is ubiquitous, with a seroprevalence of about 60 to 85% in the adult population (16,28). Acute HSV-1 infection most commonly occurs in children and young adults as a gingivostomatitis, pharyngitis, or tonsillitis and is readily transmitted through oral secretions (13). Reactivation of latent infection generally presents as oral-facial disease (cold sores) (3).…”
mentioning
confidence: 99%
“…Although HSV-1 has historically been acquired primarily in childhood, acquisition of the virus is now often seen during early adulthood (4,8,9). Seroprevalence studies from several sites worldwide have indicated that approximately 60 to 70% of adolescents have not developed antibodies to this virus and are therefore still susceptible to infection with HSV-1 (5, 7, 8).…”
mentioning
confidence: 99%
“…HSV-1 is the primary cause of oral-facial and pharyngeal herpes infections and may cause herpetic whitlow, eye infections, and disseminated disease (1,2,8,15). HSV-1 also accounts for 10 to 15% of all genital herpetic infections (3,6,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation